A Strategic Approach in Handling Information Retrieval Course for Attaining Course Outcomes – A Case Study - Sheik Abdullah, A.; Karthikeyan, P.; Selvakumar, S.; Parkavi, R. (Journal of Engineering Education Transformations, 2021)
Background: The major challenge in engineering education is to educate and train the student’s community with pedagogical practices in order to determine the notable skills to solve more complex and fragile structured problems. Innovative pedagogical practices make the students to adhere to the complex formulations of the corresponding domain and its applications. The realm of good understanding of knowledge and its deliverables can be ascertained through pedagogical practices with a focus on learner-centric activities in the classroom teaching. The actual target in teaching learning process is to make all the students to have a good exploration on the domain knowledge with success ratio. The learner success is considered to be the core metric with which we can judge the success of learner-centric activities with creativity and quality processes. Confirming the process in which the learners are engaged with the key ideas of the course to be taught makes the students to have practical implementations in Teaching-Learning process. Objective: This research work focus on the assessment and evaluation of learner-centric techniques for outcome based education upon statistical evaluation. Students of third year (VI Semester) of two consecutive batches have been analyzed for the course on Information Retrieval (14ITPS0). Two set of batches 2015-19 and 2016-20 have been considered for the assessment and analysis of Active Learning Strategies (ALS). The incorporation has been processed using the strategic approach based on daily, weekly and monthly assessments focusing on student learning criteria and their responding behaviors for 2016-20 batch. Each paradigm has been measured corresponding to the course outcomes at each level. Significant statistical analysis has been made for validating the process behind the teaching learning process. Real time case study: Considering the batch 2015-19 summary assignments, presentations has been used for the evaluation and assessment of interim assignments. The observed response from the students went well among the student’s community. All the students have been registered for the course and they too have completed the same. But, the time and success ratio in learning mechanism varied from student to student upon completion of the course. Considering the batch 2016-20 active learning strategies such as Quiz by Kahoot!, Flipped classroom activity and MOOCs course has been incorporated. Also, for MOOC’S online courses a set of two courses has been identified relevant to the subject of study such as Text Retrieval and Search engines & Text mining and Analytics. For the Research problem identification the students are allowed to choose the domain specific topics for the course on information retrieval. In this process the time and success ratio has also been observed it also varied from one student to another.